Encapsulating MWNTs into Hollow Porous Carbon Nanotubes: A Tube‐in‐Tube Carbon Nanostructure for High‐Performance Lithium‐Sulfur Batteries. (4th June 2014) - Zhao, Yi; Wu, Wangliang; Li, Jiaxin; Xu, Zhichuan; Guan, Lunhui
<x xml:space="preserve">Abstract</x> A tube‐in‐tube carbon nanostructure (TTCN) with multi‐walled carbon nanotubes (MWNTs) confined within hollow porous carbon nanotubes is synthesized for Li‐S batteries. The structure is designed to enhance the electrical conductivity, hamper the dissolution of lithium polysulfide, and provide large pore volume for sulfur impregnation. As a cathode material for Li‐S batteries, the S‐TTCN composite with 71 wt% sulfur content delivers high reversible capacity, good cycling performance as well as excellent rate capabilities. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>